Methods for Development Mobile Stunting Application: A Systematic Literature Review - Karim, Hildamayanti; Dhani Ariatmanto (Politeknik Ganesha Medan, 2024)
Stunting is a growth disorder in children. Stunting is one of the indicators of failure to thrive in toddlers caused by a chronic lack of nutritional intake in the first 1,000 days of life, from a fetus to a child aged 23 months. Based on data from the Asian Development Bank (ADB), in 2022 the percentage of stunting prevalence occurring in children aged <5 years in Indonesia reached 31.8%. So Indonesia is ranked 10th in Southeast Asia. The object of this review is to review the current literature and help researchers to find out what methods have been used in making stunting prevention applications. In a systematic search of the literature using quality databases including SpringerLink, ScienceDirect, and IEEE Xplore. The paper included in this review is a stunting prevention application information system by describing the methods most often used by researchers in making the stunting prevention application information system. There were 41 results based on the exclusion of titles and abstracts, based on the introduction and exclusion of conclusions there were 35 results, so we included 12 results for the full-text exclusion in the final analysis. So that the popular method used by researchers in Android-based stunting applications is the prototype method. Compared to other methods, prototyping is more suitable for systems that are made based on user needs.